2000
DOI: 10.22358/jafs/68116/2000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle size and extrusion of maize and sorghum on ileal digestibility and growth performance in pigs weaned at 14 and 21 days of age

Abstract: Two experiments were conducted to compare apparent ileal digestibilities and growth performance in pigs fed ground and extruded maize and sorghum. In Experiment 1, for digestibility, 24 early-weaned pigs (14 d old and 3.2 kg BW; EW) were given a terminal ileum exteriorization, and another 24 conventionally-weaned (CW) piglets (21 d old and 6.3 kg BW) were fitted with simple T-cannulae. An additional 8 piglets were employed for correction of endogenous amino acid excretions. Dietary treatments consisted of six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Similarly, Mavromichalis et al (2000) found increased G:F when decreasing feed particle size from 1.3 to 0.6 mm but a decrease in G:F when further decreasing the particle size to 0.4 mm. Chae et al (2000) found no effect of reductions in particle size on ileal digestibility of AA. In the current study, finely grinding the meal diet led to a lower feed efficiency during the first 2 wk of the trial.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, Mavromichalis et al (2000) found increased G:F when decreasing feed particle size from 1.3 to 0.6 mm but a decrease in G:F when further decreasing the particle size to 0.4 mm. Chae et al (2000) found no effect of reductions in particle size on ileal digestibility of AA. In the current study, finely grinding the meal diet led to a lower feed efficiency during the first 2 wk of the trial.…”
Section: Discussionmentioning
confidence: 77%
“…Pelleting of diets has been extensively used in commercial feed production. It is well known that pelleting improves ADG and feed efficiency in swine (Hansen et al, 1992;Wondra et al, 1992;Traylor et al, 1996;Chae et al, 1997c). In an attempt, however, to further improve the nutritional value of swine feeds, extruder and/or expander processing has been introduced for the past several decades.…”
Section: Introductionmentioning
confidence: 99%
“…Extruder/expander conditions such as degree of cooking, preconditioning, and temperature can alter the nutritional value of feeds (Chae et al, 1997d;Piao et al, 1999;Johnston et al, 1999). The feed conversion of nursery pigs fed extruded corn and sorghum was better than those fed the unextruded feed (Chae et al, 2000). Growing pigs fed extruded barley showed significantly improved growth performance and higher crude protein digestibility over pigs fed finely ground barley (Chu et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the utilization of energy may be greater in pigs fed extruded corn versus raw corn. However, the ileal digestibility of lysine or nitrogen in extruded corn is not different from that in raw corn (Herkelman et al, 1990;Chae et al, 2000). Dietary fibre reduces energy and nutrient digestibility by pigs and as a consequence, increases fecal mass and nutri-ent excretion (Shi and Noblet, 1994;Canh et al, 1998;Davidson and McDonald, 1998).…”
mentioning
confidence: 99%